War as Entertainment and Contents Tourism in Japan - Yamamura, Takayoshi; Seaton, Philip (Routledge Focus on Asia, 2022)
This book examines the phenomenon of war-related contents tourism throughout Japanese history, from conflicts described in ancient Japanese myth through to contemporary depictions of fantasy and futuristic warfare. It tackles two crucial questions: first, how does war transition from being traumatic to entertaining in the public imagination and works of popular culture; and second, how does visitation to war-related sites transition from being an act of mourning or commemorative pilgrimage into an act of devotion or fan pilgrimage? Representing the collaboration of ten expert researchers of Japanese popular culture and travel, it develops a theoretical framework for understanding war-related contents tourism and demonstrates the framework in practice via numerous short case studies across a millennium of warfare in Japan including: the tales of heroic deities in the Kojiki (Records of Ancient Matters, AD 712), the Edo poetry of Matsuo Basho, and the Pacific war through lens of popular media such as the animated film the Grave of the Fireflies. This book will be of interest to researchers and students in tourism studies and cultural studies, as well as more general issues of war and peace in Japan, East Asia and beyond.